Nucleoside supplements as treatments for mitochondrial DNA depletion syndrome - Dombi, Eszter; Marinaki, Tony; Spingardi, Paolo; Millar, Val; Hadjichristou, Nastasia; Carver, Janet; Johnston, Iain G.; Fratter, Carl; Poulton, Joanna (Frontiers in Cell and Developmental Biology, 2024)
Introduction: In mitochondrial DNA (mtDNA) depletion syndrome (MDS), patients cannot maintain sufficient mtDNA for their energy needs. MDS presentations range from infantile encephalopathy with hepatopathy (Alpers syndrome) to adult chronic progressive external ophthalmoplegia. Most are caused by nucleotide imbalance or by defects in the mtDNA replisome. There is currently no curative treatment available. Nucleoside therapy is a promising experimental treatment for TK2 deficiency, where patients are supplemented with exogenous deoxypyrimidines. We aimed to explore the benefits of nucleoside supplementation in POLG and TWNK deficient fibroblasts. Methods: We used high-content fluorescence microscopy with software-based image analysis to assay mtDNA content and membrane potential quantitatively, using vital dyes PicoGreen and MitoTracker Red CMXRos respectively. We tested the effect of 15 combinations (A, T, G, C, AT, AC, AG, CT, CG, GT, ATC, ATG, AGC, TGC, ATGC) of deoxynucleoside supplements on mtDNA content of fibroblasts derived from four patients with MDS (POLG1, POLG2, DGUOK, TWNK) in both a replicating (10% dialysed FCS) and quiescent (0.1% dialysed FCS) state. We used qPCR to measure mtDNA content of supplemented and non-supplemented fibroblasts following mtDNA depletion using 20 µM ddC and after 14- and 21-day recovery in a quiescent state. Results: Nucleoside treatments at 200 µM that significantly increased mtDNA content also significantly reduced the number of cells remaining in culture after 7 days of treatment, as well as mitochondrial membrane potential. These toxic effects were abolished by reducing the concentration of nucleosides to 50 µM. In POLG1 and TWNK cells the combination of ATGC treatment increased mtDNA content the most after 7 days in non-replicating cells. ATGC nucleoside combination significantly increased the rate of mtDNA recovery in quiescent POLG1 cells following mtDNA depletion by ddC. Conclusion: High-content imaging enabled us to link mtDNA copy number with key read-outs linked to patient wellbeing. Elevated G increased mtDNA copy number but severely impaired fibroblast growth, potentially by inhibiting purine synthesis and/or causing replication stress. Combinations of nucleosides ATGC, T, or TC, benefited growth of cells harbouring POLG mutations. These combinations, one of which reflects a commercially available preparation, could be explored further for treatment of POLG patients.